Peningkatan Kemampuan Memecahkan Masalah Siswa Kelas VIII SMPN 4 Taliwang pada Luas Bangun Datar Gabungan Berbantuan Desain Pembelajaran Elpsa melalui Aktivitas Spatial Reasoning - Kanti Warih Ade Indriani; Misbahussurur (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
Geometry is one of the material that is quite difficult in learning mathematics, evidenced by the low learning outcomes and student interest in this material. Based on the data on pre-cycle activities, the results of students' spatial abilities are low. One contributing factor is the teacher's learning methods that are less optimal in the use of visual media so students tend to only memorize formulas. Therefore the researcher applies the spatial reasoning activity on the learning framework of the ELPSA as an alternative solution to improve students' ability to solve the problem of combined flat area. This research is a class action research. The research subjects are class VIIIA. The research instrument used was pre-test / post-test and learning observation sheet. The study was conducted in 3 cycles conducted in 5 meetings. The collected data were analyzed descriptively and concluded. The results showed that learning through spatial reasoning activities in the learning framework of the ELPSA in SMPN 4 Taliwang was in accordance with the expected target seen from an increase in achievement in learning activities based on observations. Whereas the ability to solve students' problems based on the pre-test and post-test results in cycle I gained a significant increase (gain) from 0.71 which means that this score is included in the high category. Cycle II gains 0.34. This score is in the medium category. While the results of the pretest and the study gained 0.72. This means that this increase is included in the high category. The number of students who completed in the first cycle, the gain reached 0.92. high category. Cycle II gain reached 0.69 in the medium category. While the completeness of the study based on the results of the pre-test and post-test obtained a gain of 0.72. And this increase is included in the high category. Based on the results obtained it can be concluded that this study was declared successful